(3EYdGe GdCYdGe HETcGd eMGLI BOe hehSi YdjgeG GdSdGes - (3GdMSjf Hf GdMSf Hf Ydj GdGMaTs ((3eMeO Hf ESeGYjd GdCejQ s)
(3ChdgG (B:s
(3GdMeO ddg GdYXje LdGdg hHYO aEfg deG LGA ai GdMOjK GdUMjM Cfg EMJL BOe hehSi abGd ehSi CfJ CHhfG BOe hSejJg HEYdGe GdCYdGe aCbhd ggfG ebGeGf s
(3BNQgG (B:s
(3daYd GdeWdhH efg Ydjg adjS GdCKQ GdedWdhH ef Gdbhd EdG GdKhGH hbO WGd GdcdGe HYO HdhZ GdeQGe ai gPG GdebGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdeLGejYs